Diastereoselective Simmons-Smith cyclopropanations of allylic amines and carbamates. - Davies, S; Ling, K; Roberts, P; Russell, A; Thomson, J (2007)
Cyclopropanation of 3-(N,N-dibenzylamino)cyclohexene with either Zn(CH(2)I)(2)(Wittig-Furukawa reagent) or CF(3)CO(2)ZnCH(2)I (Shi's reagent) gives the corresponding syn-cyclopropane as a single diastereoisomer, whilst cyclopropanation of 3-(N-tert-butoxycarbonylamino)cyclohexene with CF(3)CO(2)ZnCH(2)I gives the corresponding anti-cyclopropane exclusively; facile N-deprotection gives access to either diastereoisomer of the trifluoroacetic acid salt of 2-aminobicyclo[4.1.0]heptane.